Solution-processed quantum dot light-emitting diodes with PANI: PSS hole-transport interlayers - Park, Young Ran; Doh, Ji Hoon; Shin, Koo; Seo, Young Soo; Kim, Yun Seok; Kim, Soo Young; Choi, Won Kook; Hong, Young Joon (ELSEVIER SCIENCE BV, 2015)
For solution-processed quantum dot light-emitting devices (QD-LEDs), poly(3,4-ethylenedioxythiophene) polystyrene sulfonate/poly(N-vinylcarbozole) (PEDOT:PSS/PVK) bilayers have been widely used as the hole injection/transport layer. The high work function of the hole transport layer is crucial for high electroluminescence efficiency with balanced electron/hole charge injection. Herein, we report improvement of the performance of QD-LEDs by inserting a polyaniline (PANI)-poly (p-styrenesulfonic acid) (PSS) (PANI: PSS) hole-transport layer between the PVK and PEDOT: PSS layers. The insertion of the PANI: PSS layer significantly shifted the electronic energy levels of the PVK layers to lower values, which reduced the energy barrier of holes traveling to the QD layer by 0.22 eV. The QD-LEDs with PANI: PSS interlayer exhibited superior electric and electroluminescent characteristics. The hole-only devices with PANI: PSS interlayer also presented high hole injection and transport capability. Ultraviolet photoelectron spectroscopy (UPS) was used to investigate the electronic energy level alignment of the QD-LEDs with/without the PANI: PSS interlayer. The device performance results of QD-LEDs and hole-only devices indicated enhanced electric and electroluminescent characteristics for the PANI: PSS-inserted QD-LEDs with high hole conduction capability, in agreement with UPS findings. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: POLYMER ELECTROLUMINESCENT DEVICES; HIGHLY EFFICIENT; WORK FUNCTION; ELECTRONIC-STRUCTURE; HIGH-PERFORMANCE; INJECTION; LAYER; INTERFACES; NANOPARTICLES; NANOCRYSTALS